A trial of a chat service for patients and their family members in an emergency department - Sejin Heo; Song-Hee Kim; Se Uk Lee; Sung Yeon Hwang; Hee Yoon; Tae Gun Shin; Hansol Chang; Taerim Kim; Won Chul Cha (BMC, 2024)
Abstract Background Effective communication between patients and healthcare providers in the emergency department (ED) is challenging due to the dynamic nature of the ED environment. This study aimed to trial a chat service enabling patients in the ED and their family members to ask questions freely, exploring the service's feasibility and user experience. Objectives To identify the types of needs and inquiries from patients and family members in the ED that could be addressed through the chat service and to assess the user experience of the service. Methods We enrolled patients and family members aged over 19 years in the ED, providing the chat service for up to 4 h per ED visit. Trained research nurses followed specific guidelines to respond to messages from the participants. After participation, participants were required to complete a survey. Those who agreed also participated in interviews to provide insights on their experiences with the ED chat service. Results A total of 40 participants (20 patients and 20 family members) sent 305 messages (72 by patients and 233 by family members), with patients sending an average of 3.6 messages and family members 11.7. Research nurses resolved 41.4% of patient inquiries and 70.9% of family member inquiries without further healthcare provider involvement. High usability was reported, with positive feedback on communication with healthcare workers, information accessibility, and emotional support. Conclusions The ED chat service was found to be feasible and led to positive user experiences for both patients and their family members.